ANALISIS KAUSALITAS ANTARA ZAKAT DAN KONSUMSI DI PROVINSI RIAU PERIODE 2015(Q1) – 2019(Q4) - Intan, Herlina; Rosyett, Rosyett; Rahmad, Richard (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to aims to determine whether there is a causal relationship between the zakat and consumsption in Riau Province for the period of 2015 (Q1) -2019 (Q4) and to find out whether there is a significant influence between the zakat and consumption in Riau Province in 2015 (Q1) – 2019 (Q4). This study uses secondary data in the form of quantive data in the form of time series, namely data zakat and data consumption. In this study, the model used is Vector Error Corection Model (VECM) technique and the Granger Causality Test to see the causality or reciprocity of the two variables studied. This study uses an analytical tool Eviews 10. From the tests that have been done, the result obtained are that between zakat and the consumption there is a one- way relationship, where the zakat affects consumption, while consumption does not affect zakat. Then in the long run it shows that the zakat has no effect on compsution. Then in lag first has a significant positive effect.Keywords: zakat, consumption, VECM, Granger Causality